Przemoc wobec kobiet a depresja - przegląd badań = Violence against women and depression - overview of research - Marta Makara-Studzińska; Agata Madej (Kazimierz Wielki University, 2015)
Makara-Studzińska Marta, Madej Agata. Przemoc wobec kobiet a depresja - przegląd badań = Violence against women and depression - overview of research. Journal of Education, Health and Sport. 2015;5(5):373-388. ISSN 2391-8306. DOI 10.5281/zenodo.17895 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A373-388 https://pbn.nauka.gov.pl/works/561541 http://dx.doi.org/10.5281/zenodo.17895 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015.   PRZEMOC WOBEC KOBIET A DEPRESJA - PRZEGLĄD BADAŃ VIOLENCE AGAINST WOMEN AND DEPRESSION - OVERVIEW OF RESEARCH Marta Makara-Studzińska, Agata Madej   Zakład Psychologii Stosowanej Uniwersytetu Medycznego w Lublinie Department of Applied Psychology, Medical University of Lublin   Streszczenie Cel. Praca jest przeglądem badań dotyczących związku pomiędzy doświadczaniem przemocy przez kobiety a ryzykiem występowania symptomów depresji. Ważnym celem było również pokazanie rozmiaru problemu jakim jest przemoc. Sprawa stosowania przemocy wobec kobiet jest współcześnie bardzo aktualna i nagłaśniana w społeczeństwie. Dane policyjne potwierdzają, iż z roku na rok coraz więcej kobiet pada ofiarami zachowań o charakterze przemocowym. Poglądy. W większości prezentowanych wyników badań został ujawniony ścisły                   związek pomiędzy doznawana przemocą a występowaniem u kobiet objawów depresyjnych. Ponadto znacznie częściej doświadczają one problemów ze zdrowiem psychicznym w postaci zespołu stresu pourazowego (PTSD), uzależnienia, zaburzeń kontaktu, zaburzeń obsesyjno-kompulsyjnych, zaburzeń odżywiania, autoagresji, trwałych zaburzeń pamięci oraz skłonności samobójczych. Sprawca przemocy stara się zniewolić swoją ofiarę i przejąć nad nią kontrolę. W ten sposób wytwarza się u niej przekonanie, że zasłużyła sobie na takie traktowanie. Życie bitych kobiet zaczyna się skupiać wokół codziennych prób przetrwania i unikania represji ze strony oprawcy. Z czasem przestają się liczyć z własnymi poglądami i myślami, przez co tracą poczucie tego, co jest dla nich dobre, a co złe. Wnioski. Uzyskane rezultaty mogą posłużyć do wyznaczania kierunków terapii dla ofiar przemocy, jak również uskutecznić działania profilaktyczne i prewencyjne. Słowa kluczowe: przemoc - przemoc wobec małżonka - depresja - kobieta maltretowana - psychoterapia.   Abstract Aim. The paper is an overview of research on the relationship between the experience of violence by women and the risk of symptoms of depression. An important goal was also to show the extent of the problem of violence. The case of violence against women is an up-to-date topic, which is publicized in society. The police data confirm that each year an increasing number of women become victims of violent behavior. Views. Most of the presented research results of studies reveal a close relationship between experiencing violence and the occurrence of   depressive symptoms in women. In addition, they are more likely to experience mental health problems in the form of post-traumatic stress disorder (PTSD), addictions, contact disorder, obsessive-compulsive disorder, eating disorders, self-harm, permanent memory disorders and suicidal tendencies. The abuser is trying to enslave the victim and take control of it. In this manner, she starts to believe that the woman deserves such treatment. The life of abused women begins to focus around everyday trials of survival and avoid reprisals from the tormentor. With time, they cease to think about their own views and thoughts, thus losing the sense of what is good and bad for them. Conclusions. The obtained results can be used to determine the directions of therapy for victims of violence, as well as to improve prophylactic and preventive measures. Keywords: violence - spouse abuse - depression - battered women - psychotherapy.